BIOLOGICAL PRODUCTION OF PLANKTON COMMUNITY IN THE MARINE REGION OF TRUONG SA ARCHIPELAGO - Tiến, Nguyễn Ngọc; Toán, Dư Văn (Vietnam Journal of Marine Science and Technology, 2014)
The biological production of plankton population in Truong Sa (Spratly) archipelago, Vietnam (6-12ON, 109-118OE) was calculated basing on energy transformed coefficients between nutrient orders. These coefficients were found by solving Nitrogen transformed cycle model in researched marine region  ecosystem. The results show that: The coarse primary power is about 69 mgC/m3/day in North-East monsoon and South-West monsoon, with about 40% fine product. Organic material synthesize ability in Southern research zone is higher than that in  the Northern zone. The fine primary power reaches from 24 to 28 mgC/m3/day in North-East monsoon and South-West monsoon. The distribution of primary power is related to the temperature field of this marine region  through seasons. The nature energy transformed coefficient is 2,5%. The secondary power changes in range 3,6-4,0 mgC/m3/day, less than 100 times primary power. The secondary power distributes relatively equal in North-East monsoon and South-West monsoon, which has the trend increasing slowly from shore to open sea.